Nyangku : Implementasi Nilai-Nilai Sosial Melalui Ritual Upacara Adat Desa Panjalu Ciamis Jawa Barat - Mirna Nur Alia Abdulah; Richi Rivaldy Setiawan Putra (Universitas Hamzanwadi, 2018)
Nyangku traditional ceremony is a form of honor through the baths of heritages of kings and ancestors Panjalu Ciamis Jawa Barat. Nyangku traditional Ceremony is still issued by the people of Panjalu Village until now. Of course, it is in the Nyangku traditional ceremony contained social values that are always implemented in the life of the people of Panjalu Village. This study is a qualitative approach with descriptive method. Data collection techniques used were interviews, observation, documentation studies, and literature studies. The researcher's informants consisted of community leaders from Panjalu Village, Kuncen Bumi Alit, and communities around Panjalu Village and the original community of Panjalu Village. The results of this study showed that social values contained in Nyangku traditional ceremony are the value of religion, mutual cooperation, moral values, the value of friendship, and aesthetic value. Social values not only implanted through the implementation of the Nyangku traditional ceremony but also through the socializations of component on the community such as Panjalu Village, family, schools, and the environment. Social values are always implemented by the people of Panjalu Village through Tabligh Akbar, marriage studies, combined in preparation for the Nyangku traditional ceremony and practicing typical arts of Panjalu Village.Keywords: Implementation, Social Values, Nyangku Traditional Ceremony